Assessing the Antioxidant, Hepatoprotective, and Iron-Chelating Potential of Perilla frutescens Seed - Sirichatnach Pakdeepromma; Komsak Pintha; Payungsak Tantipaiboonwong; Chonthida Thephinlap; Maitree Suttajit; Sawaruj Kaowinn; Napapan Kangwan; Wanwisa Suwannaloet; Kanjana Pangjit (Biomedicines)
Background/Objectives: Iron overload is a serious condition that can increase the production of reactive oxygen species (ROS), leading to oxidative tissue damage and organ dysfunction. While current pharmaceutical drugs for iron chelation have limitations, the search for natural herbs with iron-chelating properties is crucial. This study aimed to explore the various biological functions of the Perilla frutescens seed, regarding antioxidant activity and hepatoprotective and iron-chelating properties. Methods:Perilla frutescens seeds were subjected to extraction using a solvent-partitioning technique. Each fraction was evaluated for total phenolic content (TPC), total flavonoid content (TFC), and rosmarinic acid (RA) content by Folin–Ciocalteu assay, aluminum chloride colorimetric assay, and ultra-high-performance liquid chromatography (UHPLC), respectively. Antioxidant activity was assessed using DPPH, ABTS, and FRAP assays. The inhibition of lipid peroxidation was evaluated using the TBARS assay in HepG2 cells and an egg yolk model. The iron-chelating activity was examined using a ferric nitrilotriacetate (Fe3+-NTA)-binding assay, labile iron pool (LIP) level assessment, and the transferrin receptor (TfR) expression in HepG2 cells. Results: Phytochemical analysis indicated that the ethyl acetate (EtOAc) fraction had the highest TPC, TFC, and RA. This fraction demonstrated strong antioxidant properties and attenuated lipid peroxidation in HepG2 cells and egg yolk. In addition, this fraction exhibited iron-binding activity, decreased LIP levels, and induced TfR expression in iron-loaded HepG2 cells similar to the rosmarinic acid standard. Conclusions: These findings suggest that the EtOAc fraction of the Perilla frutescens seed possesses promising potential as a therapeutic agent for treating iron overload.